Self-assembled Collagen-Fibrin Hydrogel Reinforces Tissue Engineered Adventitia Vessels Seeded with Human Fibroblasts - Bijal Patel (Nature Portfolio, 2018)
Abstract Efforts for tissue engineering vascular grafts focuses on the tunica media and intima, although the tunica adventitia serves as the primary structural support for blood vessels. In surgery, during endarterectomies, surgeons can strip the vessel, leaving the adventitia as the main strength layer to close the vessel. Here, we adapted our recently developed technique of forming vascular tissue rings then stacking the rings into a tubular structure, to accommodate human fibroblasts to create adventitia vessels in 8 days. Collagen production and fibril cross-linking was augmented with TGF-β and ascorbic acid, significantly increasing tensile strength to 57.8 ± 3.07 kPa (p = 0.008). Collagen type I gel was added to the base fibrin hydrogel to further increase strength. Groups were: Fibrin only; 0.7 mg/ml COL; 1.7 mg/ml COL; and 2.2 mg/ml COL. The 0.7 mg/ml collagen rings resulted in the highest tensile strength at 77.0 ± 18.1 kPa (p = 0.015). Culture periods of 1–2 weeks resulted in an increase in extracellular matrix deposition and significantly higher failure strength but not ultimate tensile strength. Histological analysis showed the 0.7 mg/ml COL group had significantly more, mature collagen. Thus, a hydrogel of 0.7 mg/ml collagen in fibrin was ideal for creating and strengthening engineered adventitia vessels.